A Game Theoretical Model of Radiological Terrorism Defense - Shraddha Rane; Jason Timothy Harris (International Journal of Nuclear Security, 2022)
Radiological dispersal devices (RDD) pose a threat to the United States. Healthcare facilities housing high-risk radioactive materials and devices are potentially easy targets for unauthorized access and are vulnerable to malevolent acts of theft or sabotage. The three most attractive candidates for use in RDD considered in this study are: 60Co (radiosurgery devices), 137Cs (blood irradiators) and 192Ir (brachytherapy high dose radiation device). The threat posed by RDDs has led to evaluating the security risk of radioactive materials and defending against attacks. The concepts of risk analysis used in conjunction with game theory lay the foundations of quantitative security risk management. This paper develops a two player non-cooperative one-shot simultaneous defender-attacker game. The defender (healthcare facility) chooses to defend one of the three high-risk radioactive material targets and the attacker (terrorists or adversaries) chooses to attack one of the three high-risk radioactive material targets. A risk-informed approach is used to model players’ payoffs or expected utilities for each choice of strategies. A game-theoretic model (RDD game) captures the strategic interaction between competing players who act rationally to maximize their expected utility. The evaluation of the RDD game results in a von Neuman max-min strategy solution being preferable to a mixed strategy Nash equilibrium solution. The von Neumann max-min strategy solution of the defender defending cobalt and the attacker attacking cesium is found to be the most prescriptive result, thus favoring the current efforts of phasing out cesium blood irradiators and replacing them with alternative technologies. The RDD game not only gives the defender strategic options to budget scarce security resources but also helps healthcare facilities make optimal choices under severe uncertainty about the terrorist threat.
Keywords: game theory; RDD; radiological terrorism; utilities; attacker-defender; max-min